2010
DOI: 10.1007/s12603-010-0110-1
|View full text |Cite
|
Sign up to set email alerts
|

Percent body fat, fractures and risk of osteoporosis in women

Abstract: The findings are consistent with methods using DXA and/or other technologies that show percent body fat is associated with fractures of the wrist and vertebrae. Identification of risk factors is necessary for the prevention and treatment of osteoporosis and osteoporotic fractures. Estimation of percent body fat from age, height and weight may be a valid, cost-saving, and cost-effective alternative tool for screening and assessing risk of osteoporosis in settings where Dual x-ray absorptiometry (DXA) or other r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It is well-known that lipid metabolism has a close relationship with bone metabolism. The body fat percentage is positively associated with osteoporotic fracture, which leads to the emerging of an effective alternative tool for screening and assessing risk of osteoporosis by estimating body fat percentage from age, height, and weight (Wyshak, 2010 ). Biochemical analysis showed that higher level of lipids in blood is accompanied with the osteoporotic postmenopausal women (Li et al, 2015 ), while lipid-lowering drug, such as statin, could increase bone mineral density in patients and in rodents (Parhami et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that lipid metabolism has a close relationship with bone metabolism. The body fat percentage is positively associated with osteoporotic fracture, which leads to the emerging of an effective alternative tool for screening and assessing risk of osteoporosis by estimating body fat percentage from age, height, and weight (Wyshak, 2010 ). Biochemical analysis showed that higher level of lipids in blood is accompanied with the osteoporotic postmenopausal women (Li et al, 2015 ), while lipid-lowering drug, such as statin, could increase bone mineral density in patients and in rodents (Parhami et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…However they have a limitation of their use in spine. DEXA and bone densitometer enable early diagnosis of this disorder [3][4][5][6] . Recent studies on osteoporosis traced out the related factors for loss of Bone mineral density.…”
Section: Introductionmentioning
confidence: 99%
“…In osteoporosis, bone is normal but reduced in density (bone mass per unit volume of bone tissue). DEXA (Dual Energy X-ray absorptiometry) is the gold standard in quantitatively estimating bone mineral density [3][4][5] . Ultrasonic densitometers do not have a risk of radiation, are portable and there are reports to show that the sensitivity is similar to DEXA.…”
Section: Introductionmentioning
confidence: 99%